Neural Network Application in biological sequence analysis and currency prediction - Case Studies - Lee, Nung Kion (2014)
Protein sequences are composed of 20 amino acids . The twenty amino acid letters are: A, C, D, E, F, G, H, I, K, L, M, N, P, Q, R, S, T, V, W, Y. Proteins are product of genes which have many functions in our body: antibodies, enzymes, structural (hairs, tendons etc) etc.